Insights Into the Evolution of Picocyanobacteria and Phycoerythrin Genes (mpeBA and cpeBA) - Sánchez-Baracaldo, Patricia; Bianchini, Giorgio; Di Cesare, Andrea; Callieri, Cristiana; Chrismas, Nathan A. M. (Frontiers in microbiology, 2019)
Marine picocyanobacteria, and , substantially contribute to marine primary production and have been the subject of extensive ecological and genomic studies. Little is known about their close relatives from freshwater and non-marine environments. Phylogenomic analyses (using 136 proteins) provide strong support for the monophyly of a clade of non-marine picocyanobacteria consisting of and marine Sub-cluster 5.2; this clade itself is sister to marine and . The most basal lineage within the Syn/Pro clade, Sub-Cluster 5.3, includes marine and freshwater strains. Relaxed molecular clock (SSU, LSU) analyses show that while ancestors of the Syn/Pro clade date as far back as the end of the Pre-Cambrian, modern crown groups evolved during the Carboniferous and Triassic. Comparative genomic analyses reveal novel gene cluster arrangements involved in phycobilisome (PBS) metabolism in freshwater strains. Whilst PBS genes in marine are mostly found in one type of phycoerythrin (PE) rich gene cluster (Type III), strains from non-marine habitats, so far, appear to be more diverse both in terms of pigment content and gene arrangement, likely reflecting a wider range of habitats. Our phylogenetic analyses show that the PE genes ( ) evolved via a duplication of the genes in an ancestor of the marine and non-marine picocyanobacteria and of the symbiotic strains . A 'primitive' Type III-like ancestor containing and had thus evolved prior to the divergence of the Syn/Pro clade and . During the diversification of lineages, losses of genes may explain the emergence of pigment cluster Types I, II, IIB, and III in both marine and non-marine habitats, with few lateral gene transfer events in specific taxa.